DRAMATIC DISCOURSE AND ITS PRAGMATIC CHARACTERISTICS (World Bulletin of Social Sciences, 2024)
As the scope of linguistic research expands, the weight of research aimed at analyzing the occurrence of language in different contexts and the cause-and-effect relationship is also increasing. Discourse studies can also be included